2023
DOI: 10.1002/iub.2762
|View full text |Cite
|
Sign up to set email alerts
|

Lobeline: A multifunctional alkaloid modulates cholinergic and glutamatergic activities

Abstract: Developing drugs for Alzheimer's disease (AD) is an extremely challenging task due to its devastating pathology. Previous studies have indicated that natural compounds play a crucial role as lead molecules in the development of drugs. Even though, there are remarkable technological advancements in the isolation and synthesis of natural compounds, the targets for many of them are still unknown. In the present study, lobeline, a piperidine alkaloid has been identified as a cholinesterase inhibitor through chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Our previous studies demonstrated lobeline’s neuroprotective activity against glutamate mediated excitotoxicity 26 . The cell-based studies provided a valid proof for the NMDAR channel blockade activity of lobeline 26 ; however, the atomic level interaction of lobeline with NMDAR is unknown.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Our previous studies demonstrated lobeline’s neuroprotective activity against glutamate mediated excitotoxicity 26 . The cell-based studies provided a valid proof for the NMDAR channel blockade activity of lobeline 26 ; however, the atomic level interaction of lobeline with NMDAR is unknown.…”
Section: Resultsmentioning
confidence: 97%
“…Our previous studies demonstrated lobeline’s neuroprotective activity against glutamate mediated excitotoxicity 26 . The cell-based studies provided a valid proof for the NMDAR channel blockade activity of lobeline 26 ; however, the atomic level interaction of lobeline with NMDAR is unknown. Since lobeline was blocking the NMDAR channel activity, we hypothesized that lobeline may directly bind to the channel vestibule or bind to a site that can modulate the channel activity.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study, we identified lobeline as a LMNA‐binding inhibitor of c‐Myc activity in NB cells. Lobeline is a natural alkaloid derived from Lobelia inflate , and has beneficial actions via affinities for nicotinic acetylcholine receptor, vesicular monoamine transporter, opioid receptor 36 or N‐methyl‐D‐aspartate receptor 37 . Thus, it is clinically applied as a therapeutic agent for psychostimulant abuse 38 or tobacco smoking cessation 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Lobeline is a natural alkaloid derived from Lobelia inflate , and has beneficial actions via affinities for nicotinic acetylcholine receptor, vesicular monoamine transporter, opioid receptor 36 or N‐methyl‐D‐aspartate receptor. 37 Thus, it is clinically applied as a therapeutic agent for psychostimulant abuse 38 or tobacco smoking cessation. 39 Of note, lobeline is able to reverse multidrug resistance of tumour cells via inhibiting P‐glycoprotein activity.…”
Section: Discussionmentioning
confidence: 99%